2013
DOI: 10.1177/1475921713510755
|View full text |Cite
|
Sign up to set email alerts
|

Model-based detection of sensor faults under changing temperature conditions

Abstract: Nowadays, a variety of civil, aeronautic or mechanical engineering structures need regular inspections. While nondestructive testing has become state of the art, there is a trend towards online testing on demand using built-in sensors. A vast amount of in-service monitoring, as part of structural health monitoring, uses piezoelectric elements. Their deployment requires a control of the sensor performance in order to prevent false alarm. Several kinds of damage can influence the sensor performance, for example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 9 publications
1
16
0
4
Order By: Relevance
“…Using more information like the resonance behavior included in the EMI-spectrum enables the detection of minor PWAS faults and is especially valuable for the inspection of embedded transducers [40][41][42]. This is possible with the use of a physical model [4] or by utilizing purely datadriven approaches [43]. A simplified measurement of the EMI spectrum suggested in [44] and implemented, e.g., in [45] enables a quick measurement of the EMI spectrum with the same equipment as used for AU-based SHM systems.…”
Section: Methods Of Transducer Inspectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using more information like the resonance behavior included in the EMI-spectrum enables the detection of minor PWAS faults and is especially valuable for the inspection of embedded transducers [40][41][42]. This is possible with the use of a physical model [4] or by utilizing purely datadriven approaches [43]. A simplified measurement of the EMI spectrum suggested in [44] and implemented, e.g., in [45] enables a quick measurement of the EMI spectrum with the same equipment as used for AU-based SHM systems.…”
Section: Methods Of Transducer Inspectionmentioning
confidence: 99%
“…Using principal component analysis (PCA), they can be aggregated to a damage index DI model . For details, the reader is referred to [4,42].…”
Section: Model-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an aeronautic context, temperature variations as well as static loads induced on the structure during a flight can both be very important. Experiments have been carried out that focused on temperature [5][6][7][8][9][10][11][12][13][14][15][16][17] or static loads [18][19][20][21][22], but rarely simultaneously [23][24][25][26]. Regarding temperature effects, it has been observed that the effect of temperature changes consists of a shift of the piezoelectric resonance frequencies.…”
Section: Introductionmentioning
confidence: 99%